Diagnostic and Surgical Outcomes for Congenital Diaphragmatic Hernia in Neonates : A Literature Review - Wahyu Agus Prastyo; Artha Investari Nugraheni (International Medical Journal Corp. Ltd, 2025)
Introduction: The literature surrounding congenital diaphragmatic hernia (CDH) in neonates has evolved significantly over the past decade, reflecting advances in both diagnostic and surgical approaches. Literature Review : Chaudhary et al. (2019) further contribute to understanding prognostic factors associated with CDH, identifying critical indicators that correlate with survival outcomes. Their retrospective audit highlights the variability in survival rates among healthcare centers, underscoring the need for standardized protocols in managing CDH. Similarly, Raitio et al. (2021) systematically review the impact of hernia sac presence on survival outcomes, revealing that the presence of a hernia sac may confer physiological advantages, thereby improving prognosis. Long-term outcomes for CDH survivors remain a critical concern, as highlighted by Yamoto et al. (2022), who report that while survival rates have improved, these patients are at risk for various long-term complications. Cimbak and Buchmiller (2024) reinforce this by advocating for long-term follow-up clinics to manage the complex health issues that arise in CDH survivors. Their work emphasizes the necessity of a structured approach to longitudinal care that adapts to the evolving needs of this patient population. Conclusion: In conclusion, the literature reflects a multifaceted understanding of the diagnostic and surgical outcomes for congenital diaphragmatic hernia in neonates. Continued research, collaboration among healthcare professionals, and comprehensive care strategies are essential for optimizing outcomes and addressing the long-term challenges faced by CDH survivors.